Binuclear Metal Chelates of 1,2,5,6 Tetra Phyenyl-1,6-Dioxo- 3,4-Diazahexa-2,4-Diene-1,6-Dihydrazone with Ni(II). Co(II), Fe(II) and Cu(II) - Sahu, K.; Thakur, R.S. (Asian Journal of Chemistry, 2010)
A series of metal chelates of Ni(II), Cu(II), Co(II) and Fe(II) with the ligand 1,2,5,6-tetraphenyl-1 ,6-dioxo-3,4-diazahexa-2,4-diene-1,6-dihydrazone of the type Ni2L3X4, Ni2L2X4, Co2L2X4, Cu2L2X4 and FeL3X2 where X═Cl-, Br-, I-, SCN-, NO3, have been isolated, IR spectra indicate co-ordination of the ligand with the metal ions through azomethine nitrogen atoms and in binuclear complexes it spans two metal ions in a bi-bidentate manner. Electronic spectra and magnetic moment show approximately octahadral arrangement of ligands around metal ion with a distortion along the trigonal axis for the tris-complexes and along the tetragonal axis for bis-complexes.